(untitled) (Biological Sciences - PJSIR, 2010)
The preservation methods used for finding their effect on the nutrient content and organoleptic properties of Vernonia amygdalina leaves (bitter leaf), included oven drying at 40 °C without any pretreatment, blanching in steam prior to oven drying at 40 °C, light brining (25 g salt/L water), light dry salt treatment (25 g dry salt/kg leaves), light brine and vinegar treatment (50 g salt + 50 mL vinegar), and heavy salting (250 g/kg leaves), each for a duration of 14 days. Compared with drying alone, blanching before drying did not affect vitamin C, b-carotene, total carotene and ash content, but resulted in decrease of iron, sodium and calcium. Relative to the fresh vegetable, fermentation resulted in a decrease in the content of all the nutrients investigated except sodium and calcium which increased.